A Common Fixed Point Theorem in a Cone Metric Space - Jha, K. (Kathmandu University Journal of Science Engineering and Technology, 2009)
A common fixed point theorem for a pair of weakly compatible mappings is proved in a cone metric space which extends and improves various well-known similar results.